Machine perfusion in solid organ transplantation: where is the benefit? - Bruns, Helge; Schemmer, Peter (Langenbeck's archives of surgery, 2014)
Machine perfusion (MP) in solid organ transplantation has been a topic of variable importance for decades. At the dawn of organ transplantation, MP was one of the standard techniques for preservation; today’s gold standard for organ preservation for transplantation is cold storage (CS). The outcome after transplantation of solid organs has tremendously improved over the last five decades. MP has been continuously under investigation and may be an option for organ preservation in selected cases; however, there is only little evidence from clinical trials that can be used to advocate for MP as a routine organ preservation method.